2016
DOI: 10.4103/0019-509x.197725
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity and oropharynx in patients aged 18–45 years: A case–control study to evaluate the risk factors with emphasis on stress, diet, oral hygiene, and family history

Abstract: An increased risk of oral and pharyngeal cancer was seen in cases who had poor oral hygiene, stress, dental trauma, low BMI, family history of cancer, exposure to environmental carcinogens, and habit of placement of quid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Shivappa et al [ 45 ] suggested a positive interaction between a proinflammatory diet with alcohol consumption and smoking in association with oral cancer. However, Dholam and Chouksey [ 46 ] found that a diet as a risk factor for oral cancer was not statistically significant. Moreover, this study agrees with Scully's [ 5 ] research that randomized clinical trials are needed to explore the effectiveness of dietary supplementation as chemoprevention to reduce the risk of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shivappa et al [ 45 ] suggested a positive interaction between a proinflammatory diet with alcohol consumption and smoking in association with oral cancer. However, Dholam and Chouksey [ 46 ] found that a diet as a risk factor for oral cancer was not statistically significant. Moreover, this study agrees with Scully's [ 5 ] research that randomized clinical trials are needed to explore the effectiveness of dietary supplementation as chemoprevention to reduce the risk of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found an increased risk of oral cancer in patients who had suffered emotional stress. However, according to Dholam and Chouksey [ 46 ], emotional stress is a modern life symptom, and it may be responsible for delays in diagnosis due to work and family-related commitments, which probably generate patients' negligence toward their symptoms, but emotional stress would not be the core cause of oral cancer. Prospective studies with oral cancer patients would be necessary, excluding those who have scientifically proven risk factors, such as tobacco and alcohol consumption, and/or genetic factors, to show whether emotional stress alone could cause the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Shivappa et al [ 55 ] investigated the inflammatory potential of diet and risk of oropharyngeal cancer in the Italian population, finding that a proinflammatory diet and tobacco/alcohol use correlated positively with OC. However, Dholam and Chouksey [ 56 ] found no significant correlation between diet and OC. Another study by Scully [ 57 ] concluded that further randomized clinical trials were needed to elucidate the effectiveness of dietary supplementation in minimizing OC risk and eliminating the need for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral hygiene is strongly associated with oral cancer, especially in association with other risk factors, such as tobacco and alcohol. A case-control study of Indian patients aged 18-45 years reported poor hygiene for 79% of the patients with oral cavity and oropharynx cancer [141]. The risk for the development of oral cancer is decreased by 26% by dental visits [142].…”
Section: Poor Oral Healthmentioning
confidence: 99%